ZPE Ceará: política extrafiscal indutora de desenvolvimento econômico com impactos sociorregionais no município de São Gonçalo do Amarante - Queiroz, Rebeca Moreira de (2023)
The tax, exchange rate and administrative regime of Export Processing Zones (EPZ) is regulated by Law no 11.508/2007, amended by Law no 14.184/2021, which defines ZPEs as areas of free trade with abroad, as they are considered as primary zones for customs control purposes, intended for: 1) the installation of companies aimed at producing goods to be marketed internationally; 2) the provision of services linked to the industrialization of exported goods or; 3) the provision of services to be sold or intended exclusively for the foreign market. In this way, the Executive Branch can authorize its creation in less developed regions, with the aim of expanding export culture; strengthen the balance of payments; promote technological diffusion; reduce regional imbalances; and foster the country’s economic and social development. However, the Brazilian experience shows that the implementation of ZPEs has taken place at a slow pace, with ZPE Ceará being the first to come into operation, mainly because it shares the infrastructure offered by the Pecém Industrial and Port Complex (PIPC). Thus, as it is, to date, the only one in full operation, and because it is located in Pecém, a location belonging to São Gonçalo do Amarante (SGA), the question arises: how this tax incentive regime has cooperated, directly or indirectly, to the sustainable and socio-regional development of that municipality? To this end, the first chapter addressed the theoretical discussion related to the social function of taxes and extrafiscality as instruments capable of enabling one of the fundamental objectives of the Republic, anchored in the second part of section III, of art. 3o, of CF/88, that is, the reduction of social and regional inequalities, through public actions and policies, such as ZPEs in Brazil. Subsequently, in the second chapter, the historical, legislative and legal contextualization was constructed that enabled the installation of ZPEs in Brazil, as well as the modernization of Law no 11.508/2007, undertaken by Law no 14.184/2021, with the presentation of the main benefits and structural, economic and political factors linked to PIPC and CSP that influenced the operational success of ZPE Ceará. In the last chapter, data and official sources were researched regarding the economic growth of SGA, in addition to the social impacts brought by industrial development, with the aim of evaluating the design of the ZPE Ceará policy and its cost-benefit, as an induction instrument of sustainable socio-regional development. The research was guided by the hypothetical-deductive method; moving between basic and applied nature; with descriptive objectives of the problem; this taking a qualitative approach, based on the bibliographical study of specialized literature, on the examination of data and official documents in the public domain, reaching the conclusion that the ZPE Ceará has generated significant economic results, but with moderate socio-regional contributions, as it did not present characteristics that demonstrate the presence of sustainable development in the SGA, however, it has the potential to achieve it in the long term, if the necessary reforms are carried out to continue its exercise in foreign trade, in parallel with its local operations, which must continue to guide it. due to its legal and constitutional attributions.